Correction: Functionalisable acyclic cucurbiturils. Issue 10 (18th March 2019) - Bauer, Daniel; Andrae, Beatrice; Gaß, Patrick; Trenz, Danjano; Becker, Sabine; Kubik, Stefan
Abstract : Correction for 'Functionalisable acyclic cucurbiturils' by Daniel Bauer et al., Org. Chem. Front., 2019, DOI: 10.1039/C9QO00156E.